2017
DOI: 10.2147/ijn.s148179
|View full text |Cite
|
Sign up to set email alerts
|

Guided bone regeneration with asymmetric collagen-chitosan membranes containing aspirin-loaded chitosan nanoparticles

Abstract: Introduction Membranes allowing the sustained release of drugs that can achieve cell adhesion are very promising for guided bone regeneration. Previous studies have suggested that aspirin has the potential to promote bone regeneration. The purpose of this study was to prepare a local drug delivery system with aspirin-loaded chitosan nanoparticles (ACS) contained in an asymmetric collagen-chitosan membrane (CCM). Methods In this study, the ACS were fabricated using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…The physical structure and chemical properties of DBB are similar to that of natural bone and it has demonstrated positive osteoconductive properties 8,11. During clinical GBR treatment, a membranous material is usually used as a barrier to maintain the state of the graft fillings and prevent the ingrowth of fibrous tissue 1215. Unfortunately, most currently-utilized barrier membrane materials do not synergistically match the osteoconductivity of the graft implant materials due to a lack of osteoinductive function.…”
Section: Introductionmentioning
confidence: 99%
“…The physical structure and chemical properties of DBB are similar to that of natural bone and it has demonstrated positive osteoconductive properties 8,11. During clinical GBR treatment, a membranous material is usually used as a barrier to maintain the state of the graft fillings and prevent the ingrowth of fibrous tissue 1215. Unfortunately, most currently-utilized barrier membrane materials do not synergistically match the osteoconductivity of the graft implant materials due to a lack of osteoinductive function.…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55] The conditions of ACS preparation (concentrations of chitosan and TPP, the ratio of the two, the pH of the reaction, and the stirring speed) were determined in our previous study. 56 The TEM images showed that the ACS were spherical in shape with smooth surfaces and were ~100 nm in size (Figure 2A(b)).…”
Section: Results and Discussion Establishing Asa-loaded Multilayers Omentioning
confidence: 99%
“…Importantly, Chitosan (also known as glucosamine (1 ‐ 4) ‐ 2 ‐ amino ‐ b ‐ d glucose) is a natural cationic polysaccharide obtained by the deacetylation of chitin, which could be designed as scaffolds for cell accommodation, growth and differentiation (Gao et al, 2014). Usually, CS has been widely developed as a promising alternative therapeutic strategy in the areas of nerve regeneration(Zhang et al, 2018a,2018b; Yao et al, 2018), bone formation (Yao et al, 2017; Chen et al, 2017) and cartilage tissue injury repair (Sumayya and Muraleedhara Kurup, 2018) in the form of delivery carriers (Zhang et al, 2017a,2017b) and degradable scaffolds (Li et al, 2018a,b,d; Luo et al, 2018). The aforementioned functionalities of CS are due to its unique and appealing properties such as compatibility, biodegradability, nontoxicity, control release of neurotrophic factors or stem cells through scaffolds/nanoparticles.…”
Section: Chitosan Scaffold Protects Grafted Stem Cells In Vitro and Imentioning
confidence: 99%
“…Cores‐shell prepared with CS and PLGA encapsulated GDNF, which could maintain the bioactivity of GDNF for a long time, is also able to reduce the initial burst release and neutralize the acidity of PLGA degradation products and promote the PC12 cells to differentiate into neuron‐like cells in vitro (Zeng et al, 2017). In addition, porous CS‐sericin scaffold prepared with genipin for delivery of NGF showed great progress in the functional recovery of SCI in preclinical model by decreasing neuralgia, promoting structural restoration and attenuating inflammation, thereby benefiting the repair of nerve compression (Zhang et al, 2017a,2017b). The cell viability of attached neural stem cell decreased in naked NT‐3 daily addition groups, while the application of CS carrier could stably and constantly support the NSCs survival, proliferation and differentiation for at least 14 weeks(Yang et al, 2010; Yang et al, 2015).…”
Section: Sustained Release Of Neurotrophic Factors By Chitosan Complementioning
confidence: 99%